2017
DOI: 10.1021/acsami.7b01449
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembled Molecular Nanowires for High-Performance Organic Transistors

Abstract: While organic semiconductors provide tantalizing possibilities for low-cost, light-weight, flexible electronic devices, their current use in transistors-the fundamental building block-is rather limited as their speed and reliability are not competitive with those of their inorganic counterparts and are simply too poor for many practical applications. Through self-assembly, highly ordered nanostructures can be prepared that have more competitive transport characteristics; however, no simple, scalable method has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 64 publications
0
27
0
Order By: Relevance
“…We then investigate FePc nanowires, which represent a particularly interesting system as the chain length can be up to five orders of magnitude larger than for the films, a configuration that significantly improves the electronic transport properties . It has already been shown that the length of the iron chains also strongly influences the magnetic properties, with an increase in coercive field observed for increasing crystal size .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We then investigate FePc nanowires, which represent a particularly interesting system as the chain length can be up to five orders of magnitude larger than for the films, a configuration that significantly improves the electronic transport properties . It has already been shown that the length of the iron chains also strongly influences the magnetic properties, with an increase in coercive field observed for increasing crystal size .…”
Section: Resultsmentioning
confidence: 99%
“…Nanowires of Pcs with high aspect ratio can be obtained using specific conditions in OVPD and were first discovered for CuPc . They were also obtained for CoPc, and recent integration into field effect transistors has highlighted their exceptionally high on–off ratio, competitive mobility, and long lifetimes . FePc nanowires were also recently produced in a high vacuum system with high substrate temperature and argon partial pressure up to 0.02 mbar, but this resulted in shorter lengths, and has not been attributed to the η‐phase …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Anisotropic one dimensional (1D) and two dimensional (2D) nanomaterials, such as nanorods and nanosheets, have attracted significant attention in recent years due to their novel properties and various promising potential applications in the fields of energy storage, electronic and optoelectronic devices, photonic devices, antibacterial‐materials, and chemical and biological sensors . To prepare anisotropic nanomaterials, various methods have been developed including chemical vapor deposition, thermal decomposition of precursors, template‐assisted growth, swelling or exfoliation of layered materials and self‐assembly of anisotropic materials . Among these preparation methods, self‐assembly is one of the most facile and amenable to mass‐production for manufacturing anisotropic nanomaterials.…”
Section: Introductionmentioning
confidence: 87%